Using Target Cost Technology to Reduce Airline Passenger Transport Costs (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The aim of this research is to determine the total cost of travel tickets for airline companies and the extent of the impact of using the target cost technique, and the use of technology in pricing flight tickets, in addition to identifying the factors influencing the determination of the cost for passengers in the airline company, and how the cost determination and pricing process can be improved to increase the company’s position. Competitiveness, and the researcher used the deductive approach in linking the variables (target cost technique and cost reduction) with the aim of evaluating the cost system in effect in (the General Company for Iraqi Airlines) from the perspective of reducing the costs of flight tickets for passengers. The researcher also used the inductive approach and conducted a survey of studies that the research variables were presented for the purpose of extracting ideas and compiling the theoretical foundations presented in books, periodicals, conferences, and relevant research, whether Iraqi, Arab, or foreign. As for the applied aspect, reliance was placed on a set of records and statements used in the General Company for Iraqi Airlines, in addition to field visits and personal interviews. With relevant parties in the company, the research sample, outside it.   To the most important results: The management does not rely on specific strategies according to scientific foundations in building the cost of tickets for various flights and their pricing, but rather adopts the decisions of the Board of Directors in determining the amount of cost in the items of the list of flight costs and profit margin ratios according to the seasons, as well as the company's advanced costing system or techniques have not been followed in classifying its costs, which makes it difficult to adopt strategic cost management techniques such as target cost for the purpose of analyzing and measuring the real cost, as well as incorrectness in determining and calculating the cost of the trip. Based on the reality of Anfa.